No Earlier Than 9:45 A.M. A Qualitative Study of Adolescents' Experiences of Later School Start Times in Aotearoa New Zealand - Smith H; Barber C; Taylor R; Signal TL; Hetrick S; Alansari M; Oldehaver J; Galland B (Taylor and Francis Group, 2025)
OBJECTIVES: Many teenagers suffer chronic sleep loss, which could potentially be mitigated by later school start times to accommodate the natural shift in their circadian timekeeping system favoring later bedtimes. This study explored experiences of senior students from a school in Aotearoa New Zealand with later school start times. METHOD: Semi-structured interviews were conducted with 14 students, purposively sampled for equivalent numbers starting later every day (9:45 A.M.), or on just one weekday (10:00 A.M.). Transcripts were analyzed using reflexive thematic analysis. RESULTS: Four themes were identified that addressed the impact of later starts on sleep struggles, daily functioning, student autonomy, and routines and scheduling. Most perceived later starts as positively influencing their sleep quality, concentration, productivity, and personal well-being. The importance of autonomy over their learning, and impact of different start times on students' schedules was also emphasized. Major disadvantages were lack of free classes and potentially later finish times. CONCLUSIONS: The experiences of later school start times for these adolescents were largely positive across a variety of life domains. Findings support the need for sleep health to be considered within school's health education and policy to address the unmet health concerns of chronic sleep loss in teens.